Research on the Data Technology of LKJ-15 System - FANG Guanghua (Kongzhi Yu Xinxi Jishu)
Considering the present application status of LKJ infrastructure data, and the Chinese railway transportation demands such as the current railway line construction and operation adjustment, and the application of long locomotive routing, data modeling and data application technology were researched from the perspectives of technical standards, the LKJ-15 system data structure and data application. New data structure and LKJ data standardization and normalization work were also presented that meets the future development of Chinese railway transportation demands.